Target the Host, Kill the Bug; Targeting Host Respiratory Immunosuppressive Responses as a Novel Strategy to Improve Bacterial Clearance During Lung Infection - Kelly, Alanna M.; McLoughlin, Rachel M. (Frontiers in Immunology, 2020)
The lung is under constant pressure to protect the body from invading bacteria. An effective inflammatory immune response must be tightly orchestrated to ensure complete clearance of any invading bacteria, while simultaneously ensuring that inflammation is kept under strict control to preserve lung viability. Chronic bacterial lung infections are seen as a major threat to human life with the treatment of these infections becoming more arduous as the prevalence of antibiotic resistance becomes increasingly commonplace. In order to survive within the lung bacteria target the host immune system to prevent eradication. Many bacteria directly target inflammatory cells and cytokines to impair inflammatory responses. However, bacteria also have the capacity to take advantage of and strongly promote anti-inflammatory immune responses in the host lung to inhibit local pro-inflammatory responses that are critical to bacterial elimination. Host cells such as T regulatory cells and myeloid suppressor cells are often enhanced in number and activity during chronic pulmonary infection. By increasing suppressive cell populations and cytokines, bacteria promote a permissive environment suitable for their prolonged survival. This review will explore the anti-inflammatory aspects of the lung immune system that are targeted by bacteria and how bacterial-induced immunosuppression could be inhibited through the use of host-directed therapies to improve treatment options for chronic lung infections.